Personalized Assessment of the Coronary Atherosclerotic Arteries by Intravascular Ultrasound Imaging: Hunting the Vulnerable Plaque - Theodore G. Papaioannou (Journal of Personalized Medicine, 2019)
The term “vulnerable plaque„ is commonly used to refer to an atherosclerotic plaque that is prone to rupture and the formation of thrombosis, which can lead to several cardiovascular and cerebrovascular events. Coronary artery atherosclerosis has a wide variety of different phenotypes among patients who may have a substantially variable risk for plaque rupture and cardiovascular events. Mounting evidence has proposed three distinctive histopathological mechanisms: plaque rupture, plaque erosion and calcified nodules. Studies have demonstrated the characteristics of plaques with high vulnerability such as the presence of a thin fibrous cap, a necrotic lipid-rich core, abundant infiltrating macrophages and neovascularization. However, traditional coronary angiographic imaging fails to determine plaque vulnerability features, and its ability to individualize treatment strategies is limited. In recent decades, catheter-based intravascular ultrasound imaging (IVUS) modalities have been developed to identify vulnerable plaques and ultimately vulnerable patients. The aim is to individualize prediction, prevention and treatment of acute coronary events based on the identification of specific features of high-risk atherosclerotic plaques, and to identify the most appropriate interventional procedures for their treatment. In this context, the aim of this review is to discuss how personalized assessment of coronary atherosclerotic arteries can be achieved by intravascular ultrasound imaging focusing on vulnerable plaque detection.